Egypt as a woman : nationalism, gender, and politics - Baron, Beth (University of California Press, 2005)
This original and historically rich book examines the influence of gender in shaping the Egyptian nation from the nineteenth century through the revolution of 1919 and into the 1940s. In Egypt as a Woman, Beth Baron divides her narrative into two strands: the first analyzes the gendered language and images of the nation, and the second considers the political activities of women nationalists.